2000
DOI: 10.1111/j.1748-5827.2000.tb03972.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic features, confirmation and disease progression in 28 cases of lethal acrodermatitis of bull terriers

Abstract: Lethal acrodermatitis (LAD) is a genetically determined metabolic disease of bull terriers first described in the USA in the 1980s. In this study, the largest so far reported, 28 bull terriers born in the UK were diagnosed as suffering from LAD, and the clinical findings and the progression of the disease with time are described. The main characteristics of LAD are stunting, splayed digits, eating difficulties, skin disease of the face and feet, and increased susceptibility to microbial infections. In older do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
(4 reference statements)
2
23
0
2
Order By: Relevance
“…Affected pups can also exhibit abnormal behavior and diarrhea, though not all of these symptoms are present in all afflicted pups [1,3]. The current diagnostic criteria for LAD includes a combination of these features in which onset occurs at an early age [3]. One study found that five affected pups exhibited low plasma zinc levels [1], though others found that zinc levels were not significantly different from dogs with atopic dermatitis [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Affected pups can also exhibit abnormal behavior and diarrhea, though not all of these symptoms are present in all afflicted pups [1,3]. The current diagnostic criteria for LAD includes a combination of these features in which onset occurs at an early age [3]. One study found that five affected pups exhibited low plasma zinc levels [1], though others found that zinc levels were not significantly different from dogs with atopic dermatitis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The current diagnostic criteria for LAD includes a combination of these features in which onset occurs at an early age [3]. One study found that five affected pups exhibited low plasma zinc levels [1], though others found that zinc levels were not significantly different from dogs with atopic dermatitis [3]. The activity of alkaline phosphatase, a zincdependent enzyme, was also not consistently diminished in LAD pups [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected patients have variable plasma and tissue zinc concentrations and do not clinically respond to zinc supplementation. 5,7 Histologically, there is marked parakeratotic hyperkeratosis with moderate to severe epidermal hyperplasia, hypogranulosis, and dyskeratosis. Deeper keratinocytes may appear disorganized.…”
mentioning
confidence: 99%
“…This disease typically manifests as young as 6-8 weeks of age in both males and females. Affected Bull Terriers present with progressive crusting dermatitis, growth abnormalities, decreased immune function with chronic diarrhea, and bronchopneumonia 5,7,9 Survival to adulthood is rare.…”
mentioning
confidence: 99%